Cardiovascular risk after total thyroidectomy in patients with differentiated thyroid carcinoma undergoing levothyroxine replacement monotherapy - Pucci, Martina; Calzolaio, Marilena; Ghezzi, Francesco; Iannotta, Michela; Gifuni, Maria; Ruberto, Sabrina; Crescenzo, Francesca; Esposito, Roberta; Biondi, Bernadette (Frontiers in Endocrinology, 2025)
IntroductionProspective studies have demonstrated the favorable prognosis of differentiated thyroid cancer, primarily due to its low risk of recurrence and mortality. Considering these favorable outcomes, the most recent ATA guidelines recommend individualizing the degree of TSH suppression to balance the risks and benefits of LT4 therapy based on the aggressiveness of the disease. However, no studies have evaluated the cardiovascular risk in disease-free patients receiving long-term replacement doses of LT4 following the 2016 ATA guidelines.Patients and methodsThis study aimed to evaluate cardiovascular risk in disease-free athyreotic patients with differentiated thyroid cancer according to the 2021 European Society of Cardiology (ESC) guidelines. Only patients without major CV events prior to DTC diagnosis and treated with long-term LT4 therapy after the 2016 ATA guidelines were included. From a larger cohort, 300 disease-free patients who underwent total thyroidectomy—with or without radioiodine (RAI)—were selected and 102 patients were included in this study. The cardiovascular risk was assessed using the ESC 2021 scoring systems: SCORE2, SCORE2-OP, and SCORE2-Diabetes.ResultsAmong the 102 patients analyzed in detail, 14 experienced major adverse cardiovascular events (MACE) over a mean follow-up of 12.79 ± 9.13 years post-DTC diagnosis. In patients without MACE, none were classified as having a very high CV risk. A high CV risk was observed in 6% (SCORE2), 38.5% (SCORE2-OP), and 50% (SCORE2-Diabetes) of patients. Moderate CV risk was found in 34% (SCORE2), 38.5% (SCORE2-OP), and 50% (SCORE2-Diabetes), while low risk was recorded in 60% (SCORE2) and 23% (SCORE2-OP).DiscussionThese findings highlight the need for careful cardiovascular monitoring during long-term follow-up in patients with differentiated thyroid cancer. Specific cardiovascular management guidelines are needed in DTC, similar to those available for other cancer populations, to balance the risks and benefits of LT4 therapy and to identify patients at higher cardiovascular risk who may need closer monitoring.